Conductometric and 1H NMR determination of the critical micellar concentrations of two oxo-derivatives of cholic acid. Which of the two is more hydrophobic? - Poša, Mihaulj; Guzsvány, Valeria; Csanádi, János (Univerzita Pardubice, 2010)
Critical micellar concentrations (CMCs) were determined for two novel promoters of membrane permeability – 7-monoketocholic acid (7-MKC) and 12- monoketocholic acid (12-MKC), using two non-invasive (conductometry and 1H NMR relaxation experiment) methods. Studies by these methods suggest the different aggregation abilities of the investigated bile acid derivatives. In an aqueous solution, 7-MKC has a somewhat lower CMC value (43 mM) than 12-MKC (50 mM). Further, it was found that, in addition to the primary micelles, 7-MKC forms also secondary micelles. Based on the CMC value 7-MKC is more hydrophobic than 12-MKC, although the opposite data can be found in the literature. The apparent hydrophobicity of 7-MKC is a consequence of the formation of secondary micelles, shifting the monomer equilibrium to the direction of first micelles, which is manifested as a decrease in the CMC value.
Keywords: cholic acid monoketo derivatives; critical micellar concentration; primary and secondary micelles